Efektivitas Penerapan Sistem Informasi Pemerintahan Daerah dalam Pengelolaan Keuangan Daerah Kota Bekasi - Firdaus, Yuladzul Fitrohtil Huda; Cholik, M. Agus (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to determine the effectiveness of the implementation of the Regional Government Information System/Sistem Informasi Pemerintahan Daerah (SIPD) in the financial management of Bekasi City. This research uses a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The analysis of this study considers aspects of Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions based on the effectiveness indicators of information systems according to the UTAUT (Unified Theory of Acceptance and Use of Technology) theory. The results of the study indicate that the implementation of SIPD has not been effective in achieving quality regional financial management in Bekasi City. This is evidenced by the numerous obstacles in using SIPD that affect aspects of performance expectancy, effort expectancy, social influence, and facilitating conditions. The main obstacles identified include difficulties in accessing the application and a lack of features that can accommodate the entire process of regional financial management. Regarding social influence, regulatory pressure from the Minister of Home Affairs Regulation Number 70 of 2019 is the sole factor for SIPD usage. From the aspect of facilitating conditions, it is shown that the facilities owned by the Bekasi City Government are adequate for SIPD implementation, but the facilities provided by the Ministry of Home Affairs are not yet optimal, thereby hindering the application of SIPD in regional financial management.